2000
DOI: 10.1212/wnl.55.12.1854
|View full text |Cite
|
Sign up to set email alerts
|

Research evaluation and diagnosis of probable Alzheimer’s disease over the last two decades: I

Abstract: Although the diagnosis of probable AD has been used to indicate the presence of a homogeneous clinical entity, these patients can vary in presentation, onset, or clinical course. This finding is of particular importance for the understanding of the pathophysiologic basis of the disease, and for the better identification of responders to dementia treatments. Although the sensitivity for the diagnosis of AD remained above 90% over the last two decades, the specificity increased, reflecting progressive improvemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
124
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(128 citation statements)
references
References 52 publications
2
124
1
1
Order By: Relevance
“…All subjects were evaluated with standard neurological, psychiatric, and neuropsychological examinations through the University of Pittsburgh Alzheimer Disease Research Center (ADRC) as described previously (Lopez et al, 2000;Price et al, 2005), or with an equivalent evaluation at MGH (CY4 and CY5). The neuropsychological test battery is described below.…”
Section: Human Subjectsmentioning
confidence: 99%
“…All subjects were evaluated with standard neurological, psychiatric, and neuropsychological examinations through the University of Pittsburgh Alzheimer Disease Research Center (ADRC) as described previously (Lopez et al, 2000;Price et al, 2005), or with an equivalent evaluation at MGH (CY4 and CY5). The neuropsychological test battery is described below.…”
Section: Human Subjectsmentioning
confidence: 99%
“…All participants were recruited and evaluated through the University of Pittsburgh Alzheimer Disease Research Center (ADRC) and underwent detailed neurobehavioral evaluations before being given consensus diagnosis by neurologists, neuropsychiatrists, psychiatrists, and a neuroradiologist. The AD subjects met NINDS-ADRDA criteria for Probable AD (McKhann et al, 1984) and MCI subjects were classified using previously reported criteria (Lopez et al 2000). Each subject had a Mini Mental State Exam (MMSE) administered within one day of the PiB scan.…”
Section: Subjectsmentioning
confidence: 99%
“…Subjects underwent an extensive diagnostic and behavioral assessment, which has been described in detail elsewhere, 6,[25][26][27][28] and received a diagnosis of possible or probable AD utilizing the National Institute of Neurologic and Communicative Disorders and Stroke-Alzheimer Disease and Related Disorders Association criteria. 29 The rate of autopsy confirmation of AD in subjects diagnosed with possible and probable AD exceeds 90% in our center.…”
Section: Subjectsmentioning
confidence: 99%
“…29 The rate of autopsy confirmation of AD in subjects diagnosed with possible and probable AD exceeds 90% in our center. 25,26 Assessment of psychosis was performed using the Empirical Behavioral Pathology in Alzheimer Disease scale (E-BEHAVE-AD) 30 for patients from the Geriatric Psychiatry Inpatient Program, and the Behavior Rating Scale for Dementia of the Consortium to Establish a Registry for Alzheimer Disease for subjects at the ADRC. 31 Psychosis was defined by the presence of persistent hallucinations or delusions occurring at any time during the course of the dementia.…”
Section: Subjectsmentioning
confidence: 99%